Radiation Therapy for Young Children Treated With High-Dose Chemotherapy and Autologous Stem Cell Transplant for Primary Brain Tumors - Sarah A. Milgrom, MD; Jane Koo, MD; Nicholas Foreman, MD; Arthur K. Liu, MD PhD; Kristen Campbell, MS; Kathleen Dorris, MD; Adam L. Green, MD; Nathan Dahl, MD; Andrew M. Donson, BS; Rajeev Vibhakar, MD PhD; Jean M. Mulcahy Levy, MD (Advances in Radiation Oncology, 2022)
Purpose: : The role of peri-transplant radiation therapy (RT) in children with primary brain tumors is unclear. We characterized our institutional practice patterns and patient outcomes. Methods and Materials: The cohort included all patients treated with high-dose chemotherapy and autologous stem cell transplant for primary brain tumors at our institution from 2011 to 2017. Rates of local control, progression-free survival, overall survival, and radiation-associated injury were assessed. Results: Of the 37 eligible patients, 29 (78%) received peri-transplant RT. Patients treated with RT were more likely to have metastatic (P = .0121) and incompletely resected (P = .056) disease. Of those treated with RT, 13 (45%) received craniospinal irradiation (CSI) and 16 (55%) received focal RT. The median CSI dose was 23.4 Gy (interquartile range [IQR], 18-36 Gy; boost: median, 54 Gy [IQR, 53.7-55.8 Gy]) and focal RT dose was 50.4 Gy [IQR, 50.4-54.5 Gy]). Compared with the focal RT group, patients treated with CSI were older (P = .0499) and more likely to have metastatic disease (P = .0004). For the complete cohort, 2-year local control was 82% (95% confidence interval [CI], 70%-96%), progression-free survival 63% (95% CI, 49%-81%), and overall survival 65% (95% CI, 51%-82%). These rates did not differ significantly between patients treated with and without peri-transplant RT. Two cases of fatal myelopathy were observed after spinal cord doses within the highest tertile (41.4 cobalt Gy equivalent and 36 Gy). Conclusions: Peri-transplant RT was used for high-risk disease. Oncologic outcomes after RT were encouraging. However, 2 cases of grade 5 myelopathy were observed. If used cautiously, RT may contribute to durable remission in patients at high risk of relapse.